2017
DOI: 10.2174/1381612822666161216113207
|View full text |Cite
|
Sign up to set email alerts
|

Ester-Based Hydrophilic Cyclodextrin Nanosponges for Topical Ocular Drug Delivery

Abstract: The ester-based hydrophilic cyclodextrin-based nanosponge derivative can be used as a drug delivery system in topical ocular drug delivery, to improve stability, solubility and corneal permeation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The differences in the release patterns show that the migration of the guest molecules and the ability of NSs to entrap the drug molecules depend on the crosslinking between the cyclodextrin monomers. A higher concentration of cross-linker results in hindering of the interaction of MPH and CYT with the cavities of the NSs, thus reducing their effectiveness as a drug carrier [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the release patterns show that the migration of the guest molecules and the ability of NSs to entrap the drug molecules depend on the crosslinking between the cyclodextrin monomers. A higher concentration of cross-linker results in hindering of the interaction of MPH and CYT with the cavities of the NSs, thus reducing their effectiveness as a drug carrier [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The β-CD:cross-linker molar ratio influence on drug release was investigated. It was found that the β-CD and cross-linker affect the nano-channels produced and, therefore, the extent of hydrogel swelling, drug loading capacity, and the rate of drug release [34,35]. Moreover, to control and design the delivery kinetics, deep knowledge of the cross-linking properties of polymeric structures is a mandatory step [36].…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy in attenuated total reflectance geometry (FTIR-ATR), CHNS/O analysis, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) analysis, light scattering analysis [133], low-frequency Raman scattering [134], high-resolution magic angle spinning (HRMAS) NMR spectroscopy, carbon-13 nuclear magnetic resonance ( 13 C NMR), proton nuclear magnetic resonance ( 1 H NMR), thermogravimetric analysis (TGA), potentiometric titration, Brunauer-Emmett-Teller (BET) analysis, transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) have been extensively employed in the studies over the years. In addition, the nano-formulations developed need to be evaluated as far as encapsulation efficiency and loading capacity, stability, in vitro drug release, in vivo pharmacokinetic release, efficacy and toxicity are concerned in order to ensure quality and efficacy [35,37,53,56,57,73,76,78,98,109,122,125,[135][136][137][138][139][140].…”
Section: From 2016 To Present: State-of-the-art and Future Prospects Of Nanospongesmentioning
confidence: 99%
“…( 1 H NMR), thermogravimetric analysis (TGA), potentiometric titration, Brunauer-Emmett-Teller (BET) analysis, transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) have been extensively employed in the studies over the years. In addition, the nano-formulations developed need to be evaluated as far as encapsulation efficiency and loading capacity, stability, in vitro drug release, in vivo pharmacokinetic release, efficacy and toxicity are concerned in order to ensure quality and efficacy [35,37,53,56,57,73,76,78,98,109,122,125,[135][136][137][138][139][140].…”
Section: From 2016 To Present: State-of-the-art and Future Prospects Of Nanospongesmentioning
confidence: 99%